Bio-inspired color-changing and self-healing hybrid hydrogels for wearable sensors and adaptive camouflage. Issue 1 (13th December 2022) - Liu, Han; Yu, Long; Zhao, Bingqian; Ni, Yezhou; Gu, Peng; Qiu, Hua; Zhang, Wan; Chen, Kunlin
Abstract : A novel color-changing and self-healing hybrid hydrogel was prepared by mixing the thermochromic dye microcapsules and photochromic dye microcapsules with the multi-branched polyacrylate. Abstract : Hydrogels have been extensively investigated for their unique mechanical and ionic conductive properties. Currently, conventional hydrogels are not sufficiently durable for use and do not respond sensitively to environmental stimuli. Accordingly, the development of a hybrid hydrogel exhibiting self-healing ability and environmental responsiveness is of critical significance in broadening its application in smart wearable devices. For the formation of a color-changing and self-healing hybrid hydrogel, thermochromic dye microcapsules and photochromic dye microcapsules were mixed with a multi-branched polyacrylate and zinc sulphate in this study. This hybrid hydrogel exhibited an excellent sensing property, and can be applied to wearable device for monitoring the actions of human joints or faces. Even though the hybrid hydrogel was damaged during its application, the damaged parts of the hydrogel were self-repaired, which was dependent on the powerful ionic bonds and multi-hydrogen bonds among the polyacrylate, zinc ions, as well as microcapsules. Furthermore, under the synergistic effect of microcapsules and polyacrylate, the rapid change of color and current under thermal or UV stimulus facilitates monitoring human physiological health, as well as achieving adaptive camouflage. This smart hybrid hydrogel exhibiting self-healing, conductive, and color-changing properties has promising applications in human body monitoring, safety warning, adaptive camouflage, and artificial intelligence for wearable electronic devices.